Monitoring House Fly (Diptera: Muscidae) Activity on Animal Facilities. Issue 6 (2nd November 2020) - Gerry, Alec C
Abstract: Monitoring house fly (Diptera: Muscidae) activity on animal facilities is a necessary component of an integrated pest management (IPM) program to reduce the negative impacts of these flies. This article describes monitoring methods appropriate for use on animal facilities with discussion of monitoring device use and placement. Action thresholds are presented where these have been suggested by researchers. Sampling precision is an important aspect of a monitoring program, and the number of monitoring devices needed to detect a doubling of fly activity is presented for monitoring methods where this information is available. It should be noted that both action thresholds and numbers of monitoring devices will be different for every animal facility. Suggested action thresholds and numbers of monitoring devices are presented only to provide guidance when initiating a fly monitoring program. Facility managers can adjust these values based upon the fly activity data recorded at their facility. Spot cards are generally recommended as an easy-to-use method for monitoring fly activity for most animal facilities. Fly ribbons or similar sticky devices are recommended where several pest fly species may be abundant and identifying the activity of each species is important, but a sampling period of <7 d may be needed in dusty conditions or when fly density is high. Fly ribbons are not recommended for outdoor use. Insecticide-baited traps may be used in outdoor locations where environmental conditions limit the use of spot cards, fly ribbons, and sticky traps.